QSC+ 2.0: an improved version of quick calculator guideline for basic statistics / Hazfina Mohamed Idris ... [et al.] - Mohamed Idris, Hazfina; Johar, Nurain; Poli, Firus Musfirah; Mohd Jamil, Nor Hilaliyah; Jafri, Fakhira; Lau Chui Ting, Grace (2022)
Mathematics and statistics are obligatory subjects in most courses of a university. It is essential for students to have the skills to fully utilise the function of a scientific calculator as it is an important tool that will help them to solve mathematics and statistical problems. However, they will not be able to fully utilise a scientific calculator if there is no clear guideline on how to use the functions built in the calculator. QSC+ version 2.0 was developed as one of the informative platforms to guide students in using scientific calculator to solve basic statistical calculations. This online based platform provides its users guidelines through the step-by-step videos and learning check exercises to test their understanding. Thus, we have collected feedback from basic statistics course students in terms of their satisfaction using the QSC+2.0 platform. Questionnaires were distributed to the selected 26 respondents after they had browsed the platform. All the respondents (57% strongly agree, 43% agree) found the platform attractive. However, 4% of the respondents faced problems while using the platform. Additionally, from the gathered data, all the respondents would recommend the QSC+2.0 to others, and they believed that the platform is useful for learning basic statistics. In conclusion, the upgraded QSC+2.0 is a beneficial and feasible platform to provide knowledge sharing sessions for the students and concurrently convenient for the educators in assisting them to teach basic statistics.